Magnolia vargasiana (Magnoliaceae), a new Andean species and a key to Ecuadorian species of subsection Talauma, with notes on its pollination biology - Vázquez-García, J.-Antonio; Neill, David A.; Asanza, Mercedes (Phytotaxa, 2015)
Magnoliaceae Jussieu (1789: 280) consist of ca. 330 species worldwide, nearly half of them in the New World (Vázquez-García et al. 2014). There is no agreement on the internal classification, including the number of sections (0–11), genera (1–13), subgenera (0–9) and subfamilies (0–2) (Figlar & Nooteboom 2004; Xia et al. 2008, Romanov & Dilcher 2013) and despite various phylogenetic studies of Magnoliaceae in the last two decades, classification of the family has not reached a consensus (Qiu et al. 1993, 1995; Kim et al. 2001; Azuma et al. 2001, Li & Conran 2003, Nie et al. 2008, Kim & Suh 2013). Here we follow the classification of Figlar & Nooteboom (2004).